A Contemplation on Avicenna’s Arguments on Immateriality of the Soul - Mehraki, Bahador (MAQOLAT: Journal of Islamic Studies, 2025)
Abstract Total intellectual immateriality of rational soul is one of the major subjects in philosophy and anthropology among Muslims, especially Avicenna. Avicenna has provided several arguments to prove the intellectual immateriality of rational soul, using the position and insensibility of intelligible forms, the unlimited power of the soul in the perception of intelligible forms, and rational soul being needless of physical tools in some of its perceptions. In the present study, the mentioned arguments are explored and criticized, demonstrating that they cannot prove the total intellectual immateriality of the rational soul, that is, its complete lack of matter and the properties of matter (volume and mass). Therefore, other points of view about the rational soul - for example, those of Mulla Sadra Shirazi -which state the materiality of the soul at the time of its creation and its subsequent immateriality as a result of substantial motion- should be recruited.